Analisis Determinan Intensitas Energi Di Indonesia Tahun 2000-2020 - Dwi Resti Pratiwi (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2022)
Energy intensity can be reduced by increasing efficiency in the use of energy. The aim of this study is to analyze the energy intensity in Indonesia for the period 2000-2020. It investigates the impact of real GDP per capita, energy prices, trade openness, and foreign direct investment on energy intensity over the period 2000-2020. VAR/VECM analysis is used to determine how economic variables affect aggregate intensity. The results of this study indicate that real GDP per capita and trade openness have a negative impact on energy intensity, while energy prices and foreign direct investment have a positive effect on energy intensity. Thus, the study suggests that the Government of Indonesia should consider reducing energy consumption in non-renewable energy sources by investing in renewable energy sources. Besides, by understanding the determinants of energy intensity, the government should create an energy policy framework to reduce the sector’s carbon intensity and improve energy efficiency.